Nanospot welding of carbon nanotubes using near-field enhancement effect of AFM probe irradiated by optical fiber probe laser1. Issue 70 (31st July 2015) - Yang, Lijun; Cui, Jianlei; Wang, Yang; Hou, Chaojian; Xie, Hui; Mei, Xuesong; Wang, Wenjun; Wang, Kedian
<x xml:space="preserve">Abstract</x> The carbon nanotubes interconnection can be achieved by the new nanospot welding method with the near-field enhancement effect of the metallic AFM probe tip irradiated by optical fiber probe laser.